The institute of criminal misdemeanor as a form of criminal offense - Chornyi, Andrii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2022)
The article defined the concept of criminal misconduct, its components, as well as related to its commission of criminal legal consequences; legal analysis of legislative amendments to the Criminal and Criminal Procedural Codes of Ukraine; the legislative acts of Ukraine establishing criminal liability for criminal misconduct are analyzed. The purpose of the research is to conduct a comprehensive doctrinal analysis of the theoretical and legal basis for the introduction of the institute of criminal offenses and criminal liability for their commission, as well as legal analysis of legislative changes due to the latest form of criminal offenses. Thus, the Criminal Procedure Code of Ukraine in 2012 introduced the institution of criminal offenses, but this institution required the adoption of the Law of Ukraine "On Criminal Offenses" to enter into force. Numerous bills on criminal offenses, which were considered for eight years, had different meanings and visions about the essence of the institution of criminal offense and its place in criminal law, so only on 01.07.2020 the concept of criminal offense was introduced into current criminal law of Ukraine. Regarding the definition of the concept of criminal misconduct according to Part 1 of Article 12 of the Criminal Code Criminal offenses are divided into criminal misdemeanors and crimes. Part 1 of Article 11 of the Criminal Code indicates that a criminal offense is a socially dangerous criminal act (action or omission) provided by this Code, committed by the subject of the criminal offense. Thus, a criminal offense is one of the forms of a criminal offense The introduction of these substitutions is essentially a change in the classification of criminal offenses, where an act involving a punishment less severe than imprisonment or a fine of up to three thousand tax-free minimum incomes is called a criminal offense, and moderate crimes are renamed minor. It should be noted that the lack of terminology of criminal misconduct in the relevant provisions of the Constitution of Ukraine hinders the introduction of the institution of criminal misconduct in full.